2020
DOI: 10.1002/hrdq.21418
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying, socially aversive attitudes, reduced work group effectiveness, and organizational frustration

Abstract: Given that workplace bullying can harm employees' thoughts, perceptions, and experiences, this study explored how bullying triggers socially aversive attitudes in victims, as well as diminished work group effectiveness and increased organizational frustration. Using time-lagged data collected from research panelists, the hierarchical regression results indicated that workplace bullying can lead to distrust of others, a self-focused strategy based on the belief that workplace advancement is political, and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 144 publications
(297 reference statements)
0
7
0
Order By: Relevance
“…Research studies have also revealed a significant linkage between bullying and work alienation (Kerse and Babadag, 2019;Kilic et al, 2017;Demirel et al, 2012). As perpetrators often form cliques to the detriment of targets who have lesser power and influence, bullying also manifests as collective exclusion (Valentine et al, 2021;Branch et al, 2013). Exposure to bullying, thus, alienates the targets as they feel powerless and vulnerable and struggle to defend themselves against the ill-treatment (Anasori et al, 2020).…”
Section: Hypotheses Development 31 Workplace Bullying Work Alienation...mentioning
confidence: 99%
See 2 more Smart Citations
“…Research studies have also revealed a significant linkage between bullying and work alienation (Kerse and Babadag, 2019;Kilic et al, 2017;Demirel et al, 2012). As perpetrators often form cliques to the detriment of targets who have lesser power and influence, bullying also manifests as collective exclusion (Valentine et al, 2021;Branch et al, 2013). Exposure to bullying, thus, alienates the targets as they feel powerless and vulnerable and struggle to defend themselves against the ill-treatment (Anasori et al, 2020).…”
Section: Hypotheses Development 31 Workplace Bullying Work Alienation...mentioning
confidence: 99%
“…Work alienation and emotional exhaustion are two critical psychological conditions that determine employee well-being and burnout at work. Researchers have documented how work alienation adversely influences several positive work-associated employee outcomes like performance, affective commitment and altruistic behaviors (Usman et al, 2020;Valentine et al, 2021;Vukeli c et al, 2019). Additionally, emotional exhaustion has also been regarded as an important element of burnout with critical negative consequences such as reduced mental well-being, commitment, job performance and heightened exit intentions (Anasori et al, 2020;Bayighomog et al, 2021;Gull et al, 2023;Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies further indicate that when one or several members of a team are subjected to bullying in the workplace, performance levels drop in teamwork environments where cooperation is essential to attain set goals and objectives (Brotheridge, 2013;Valentine et al, 2021). Coyne et al (2004) conducted a study to explore the effects of bullying in the workplace in a teamwork contextlessened levels of work performance were reported in teams that experienced bullying compared to teams that had not encountered any forms of bullying.…”
Section: Workplace Bullying and Team Performancementioning
confidence: 99%
“…Vibrant HRD research has been conducted on various workplace mistreatment, such as workplace incivility ( e.g., Bartlett & Bartlett, 2011; Gupta et al, 2020; Valentine et al, 2020), harassment (e.g.,Goldberg et al, 2019), microaggressions (e.g., Byrd, 2016; Pitcan et al, 2018), and even violence (e.g., Collins, 2011). However, compared to the relatively well-trodden concepts of other workplace mistreatments, the topic of backlash has been given short shrift by HRD researchers except for Hill’s (2009) invitation for more scholarly attention to it.…”
mentioning
confidence: 99%